NIR luminescence from sol-gel Er3+ doped SiO2:GeO2 transparent gels, nanostructured powders and thin films for photonic applications - Maia, Lauro J. Q.; Gonçalves, Rogéria R.; Gomes, Anderson S. L.; Ribeiro, Sidney J. L. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2015)
Samples of (1 - x)SiO2:xGeO2 compositions, containing x = 10 and 20, and doped with Er3+, were prepared by a simple sol-gel route. Homogeneous and transparent gels were synthesized and xerogels were obtained by gel annealing from 700 °C to 1100 °C. Films exhibiting high transmittance in the visible and near infrared were deposited by spin-coating technique using the colloidal precursors. The materials were characterized structurally and microstructurally by some techniques. Spherical completely amorphous and tetragonal GeO2 nanocrystals from 3.7 nm to 25.0 nm in diameter embedded in silica-rich amorphous phase materials were obtained. The optical properties were studied by transmission spectra from ultraviolet to near infrared region, photoluminescence measurements in the infrared region, and the average lifetime of the metastable state 4I13/2 of Er3+ ions were determined. The 1 mol% Er3+ doped host with x = 20 have an infrared emission 4.9 times higher than the compound containing x = 10, and the Er3+ 4I13/2 level present lifetime between 15.0 ms and 7.5 ms. The optical band gap and refractive index values were determined, as well as the Sellmeier parameters. Finally, rib channel waveguides using femtosecond laser etching technique on silica substrates were obtained with width of 15 mm. The 1 mol% Er3+ doped 80SiO2:20GeO2 compounds can be applicable in integrated optical systems.
Keywords: Er-doped SiO2:GeO2; Nanocomposite; Optical and structural properties; Optical waveguide; Simple sol-gel route